2011
DOI: 10.1039/c1dt10380f
|View full text |Cite
|
Sign up to set email alerts
|

Metal-based anti-diabetic drugs: advances and challenges

Abstract: The current status and likely future directions of complexes of V(V/IV), Cr(III), Mo(VI), W(VI), Zn(II), Cu(II), and Mn(III) as potential oral drugs against type 2 diabetes are reviewed. We propose a unified model of extra- and intracellular mechanisms of anti-diabetic efficacies of V(V/IV), Mo(VI), W(VI), and Cr(III), centred on high-oxidation-state oxido/peroxido species that inhibit protein tyrosine phosphatases (PTPs) involved in insulin signalling. The postulated oxidative mechanism of anti-diabetic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 255 publications
(237 reference statements)
0
95
0
Order By: Relevance
“…27 Of note, Cr(III) has even been used as an antidiabetic agent. 28 In summary in this study we have demonstrated, using human liver microsomes, that two (η 6 -PZQ)Cr(CO) 3 derivatives, which were previously shown to have in vitro activity against S.…”
Section: Discussionmentioning
confidence: 99%
“…27 Of note, Cr(III) has even been used as an antidiabetic agent. 28 In summary in this study we have demonstrated, using human liver microsomes, that two (η 6 -PZQ)Cr(CO) 3 derivatives, which were previously shown to have in vitro activity against S.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic processing of organic drugs reduces their presence until they have been completely metabolized or excreted. In the case of metal based drugs the fate of the drug (the metal complex) involves the formation of new metal-coordination complexes 3, 8, 12, 14, 19, 20, 29, 30, 36, 37 . Since the metal ions do not participate in the same reactions as organic compounds, they either persist with a continued pharmaceutical response, accumulate in a non-active silent reservoir or are excreted.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to expectations, it is very important to mention that a release of the Cr(CO) 3 core cannot be responsible for the observed toxicities. Assuming that all chromium given to mice was transformed into Cr(III) (note that this transformation involves the passage through other oxidation states), the amount of Cr(III) would not be sufficient to kill mice since Cr(III) salts have LD 50 values in the range 3.2-15 g/kg when given orally to mice [53,56]. Taken together, the toxicity observed in mice during the in vivo studies may be rationalized with the parasitic infection itself and is most likely not related with the administration of the chromium compounds.…”
Section: Praziquantel (Pzq) the Major Metabolite (Pzq-oh) And The mentioning
confidence: 99%